2021
DOI: 10.1029/2021gc009807
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lateral and Stress‐Dependent Viscosity Variations on GIA Induced Uplift Rates in the Amundsen Sea Embayment

Abstract: Accurate GIA models are required for correcting measurements of mass change in Antarctica and for improving knowledge of the sub-surface, especially in areas of large current ice loss such as the Amundsen Sea Embayment(ASE). Regionally, seismic and gravity data suggests lateral differences in viscosity (3D). Furthermore, mantle flow laws allow for a stress-dependent effective viscosity which changes over time (3D-s). In this study we investigate whether models with 3D/3D-s have significant effects on the uplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 72 publications
0
19
1
Order By: Relevance
“…Such rheological complexity may also contribute to, or even generate, confined regions with effectively low viscosity, of the sort that we have modeled here. Regardless, the impact of rheological complexity needs more investigation and could help to reconcile models and observations of uplift (Adhikari et al., 2021; Blank et al., 2021; Lau et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such rheological complexity may also contribute to, or even generate, confined regions with effectively low viscosity, of the sort that we have modeled here. Regardless, the impact of rheological complexity needs more investigation and could help to reconcile models and observations of uplift (Adhikari et al., 2021; Blank et al., 2021; Lau et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Such rheological complexity may also contribute to, or even generate, confined regions with effectively low viscosity, of the sort that we have modeled here. Regardless, the impact of rheological complexity needs more investigation and could help to reconcile models and observations of uplift (Adhikari et al, 2021;Blank et al, 2021;Lau et al, 2021). Bevis et al (2012) found that in most of coastal Greenland the elastic response to contemporary ice mass change matches the historic viscous response or dominates the uplift signal.…”
Section: Factors Affecting Uplift From Contemporary Ice Meltmentioning
confidence: 99%
“…The viscosity for sub‐centennial timescale mantle deformation resolved by our constraining data is roughly one order of magnitude smaller than the upper mantle viscosity typically inferred in GIA analysis of relative sea‐level data. Future glacial loading studies should, therefore, consider a more comprehensive than the Maxwell mantle rheological model that captures mantle relaxation across a range of timescales (Blank et al., 2021; Caron et al., 2017; Ivins et al., 2020; Lau et al., 2020; Lau & Holtzman, 2019). Laboratory experiments of rock creep at high temperature and pressure environments (e.g., Faul & Jackson, 2015; Kohlstedt & Hansen, 2015) and recent studies of post‐seismic mantle flow (e.g., Liu et al., 2020; Muto et al., 2019; Pollitz, 2019) suggest the necessity of considering such higher‐order constitutive relations.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore postulate the importance of alternative mantle relaxation processes that are either governed by inherently transient rheology (Ivins et al., 2020; Lau et al., 2020) or by non‐linear stress‐dependent rheology (Blank et al., 2021). Such enhancement of the relaxation process acts to lower the effective viscosity on timescales of decades to centuries and thus produce more rapid uplift rates for post‐MWP mass changes.…”
Section: Post‐mwp Loading and Solid Earth Responsementioning
confidence: 99%
See 1 more Smart Citation